Functional representation for the grand partition function of a multicomponent system of charged particles: Correlation functions of the reference system - Patsahan, O.V.; Mryglod, I.M. (Condensed Matter Physics, 2006)
Based on the method of collective variables (CV) with a reference system, the exact expression for the functional
of the grand partition function of a m-component ionic model with charge and size asymmetry is found.
Particular attention is paid to the nth particle correlation functions of the reference system which is presented
as a m-component system of “colour” hard spheres of the same diameter. A two-component model is considered
in more detail. In this case the recurrence formulas for the correlation functions are found. A general
case of a m-component inhomogeneous system of the “colour” hard spheres is also analysed. На основi методу колективних змiнних з системою вiдлiку, отримано точний вираз для функцiоналу
великої статистичної суми m-компонентної iонної моделi з асиметрiєю розмiрiв та зарядiв. Особлива увага придiляється n-частинковим кореляцiйним функцiям системи вiдлiку, яка представляється
як m-компонентна система “кольорових” твердих сфер однакового дiаметру. Детально розглянуто
випадок двокомпонентної моделi, для якої отримано рекурентнi формули для кореляцiйних функцiй.
Також проаналiзовано випадок m-компонентної неоднорiдної системи “кольорових” твердих сфер.